2015
DOI: 10.1038/srep13013
|View full text |Cite
|
Sign up to set email alerts
|

Rhus coriaria induces senescence and autophagic cell death in breast cancer cells through a mechanism involving p38 and ERK1/2 activation

Abstract: Here, we investigated the anticancer effect of Rhus coriaria on three breast cancer cell lines. We demonstrated that Rhus coriaria ethanolic extract (RCE) inhibits the proliferation of these cell lines in a time- and concentration-dependent manner. RCE induced senescence and cell cycle arrest at G1 phase. These changes were concomitant with upregulation of p21, downregulation of cyclin D1, p27, PCNA, c-myc, phospho-RB and expression of senescence-associated β-galactosidase activity. No proliferative recovery w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
51
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 59 publications
(73 reference statements)
5
51
0
Order By: Relevance
“…When the concentration of the sumac extract increased, the number of live cells decreased. Our results were consistent with the previously anticancer studies with sumac (1,9,24), the anticancer and growth inhibitory effects of the extracts may be due to the fact that rich secondary metabolites components of the R. coriaria L., as described previously (12,25,26).…”
Section: Discussionsupporting
confidence: 93%
“…When the concentration of the sumac extract increased, the number of live cells decreased. Our results were consistent with the previously anticancer studies with sumac (1,9,24), the anticancer and growth inhibitory effects of the extracts may be due to the fact that rich secondary metabolites components of the R. coriaria L., as described previously (12,25,26).…”
Section: Discussionsupporting
confidence: 93%
“…As one of the most important intracellular pathways, MAPK pathway is frequently activated in a number of cancers and is responsible for the resistance of cell growth, autophagy [9], apoptosis [8, 23], metabolism, and invasion [24]. In the present research, it is discovered that RA could effectively activate p38 MAPK pathway (Figure 2(d)).…”
Section: Discussionmentioning
confidence: 52%
“…p38 MAPK pathway has been proved to be associated with induction of apoptosis [7, 8] and autophagy [9]. We therefore speculated that RA might induce apoptosis and autophagy in SGC-7901 cells by suppressing the p38 MAPK signaling pathway.…”
Section: Resultsmentioning
confidence: 97%
“…El Hasasna et al. (2015, 2016) reported that the ethanolic extract obtained from Lebanese R. coriaria showed interesting antiproliferative activity against T47D, MCF‐7 and MDA‐MB‐231 breast cancer cells. The results showed that T47D and MDA‐MB‐231 cells were more sensitive to the investigated ethanolic extract than MCF‐7 cell lines.…”
Section: Bioactivity Studiesmentioning
confidence: 99%